2016
DOI: 10.1007/s13277-016-4825-4
|View full text |Cite
|
Sign up to set email alerts
|

Immunization of stromal cell targeting fibroblast activation protein providing immunotherapy to breast cancer mouse model

Abstract: Unlike heterogeneous tumor cells, cancer-associated fibroblasts (CAF) are genetically more stable which serve as a reliable target for tumor immunotherapy. Fibroblast activation protein (FAP) which is restrictively expressed in tumor cells and CAF in vivo and plays a prominent role in tumor initiation, progression, and metastasis can function as a tumor rejection antigen. In the current study, we have constructed artificial FAP(+) stromal cells which mimicked the FAP(+) CAF in vivo. We immunized a breast cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…In this context, it is conceivable that surface markers expressed mainly, if not exclusively, by MSC should be considered to regulate the TME. Indeed, FAP, CD73, and CD105 can be considered as suitable markers to target MSC [11,13,14,131,132,133,134,135,136,137,138,139,140,141,142,143,144,145,146,147,148,149,150]. In hematological malignancies, but also in solid tumors, the administration of immunomodulatory drugs (IMiDs) derived from their prototype Thalidomide to CC-122 has given very attractive results because these compounds can hit MSC besides tumor cells [151,152,153].…”
Section: Drugs That Can Influence Msc-mediated Immune Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, it is conceivable that surface markers expressed mainly, if not exclusively, by MSC should be considered to regulate the TME. Indeed, FAP, CD73, and CD105 can be considered as suitable markers to target MSC [11,13,14,131,132,133,134,135,136,137,138,139,140,141,142,143,144,145,146,147,148,149,150]. In hematological malignancies, but also in solid tumors, the administration of immunomodulatory drugs (IMiDs) derived from their prototype Thalidomide to CC-122 has given very attractive results because these compounds can hit MSC besides tumor cells [151,152,153].…”
Section: Drugs That Can Influence Msc-mediated Immune Regulationmentioning
confidence: 99%
“…Several kinds, compositions, and modes of administration of anti-tumor vaccines have been used with different results [160,161,162,163,164,165,166,167]. More recently, the focus of anti-tumor vaccines has been moved from tumor cells to TME too [7,9,10,131,132,133,134,135,136,137,138,139,140,141,142,143,144,145,146,147,148,149,150,151,152,153,154,155,156,157,158,159,160,161,162,163,164,165,166,167,168,169,170,171,172,173,174,175]. Indeed, the possibility of targeting tumor endothelial cells or the VEGF signaling axis with specific vaccines has been assessed in preclinical studies, and clinical trials are ongoing [168].…”
Section: Msc As Target Cells For Anti-tumor Vaccinesmentioning
confidence: 99%
“…With these observations in mind, interfering with CAF activity has been envisioned as an antimetastatic pharmacological strategy . A phase I study showed that the gelatinase FAP expressed in CAFs selectively accumulates in the tumor area, and that vaccination with FAP+ stromal cells significantly inhibits the growth of allograft tumors and reduces lung metastasis in a breast cancer‐bearing mouse model . These results support the idea that developing anti‐CAF reagents would interfere with tumor malignancy in breast cancer.…”
Section: Introductionmentioning
confidence: 76%
“…Maintaining appropriate balances between RNA-BPs that degrade or stabilize ARE- or GRE-containing mRNAs is a mechanism to ensure appropriate expression of these transcripts and to sustain healthy homeostasis. Understanding the crosstalk between CELF1, ZFP36, ELAVL1 and other RNA-BPs may uncover novel therapeutic strategies to fine-tune the balance in cell growth and cell death pathways involved in human cancer [201, 202]. In the future, more work needs to be done to develop interventions targeting post-transcriptional mechanisms involved in cancer pathogenesis.…”
Section: Discussionmentioning
confidence: 99%